Simulation of plasma–surface interactions in a fusion reactor by means of QSPA plasma streams: recent results and prospects. (1st August 2016) - Garkusha, I E; Aksenov, N N; Byrka, O V; Makhlaj, V A; Herashchenko, S S; Malykhin, S V; Petrov, Yu V; Staltsov, V V; Surovitskiy, S V; Wirtz, M; Linke, J; Sadowski, M J; et al.
Abstract: This paper is devoted to plasma–surface interaction issues at high heat-loads which are typical for fusion reactors. For the International Thermonuclear Experimental Reactor (ITER), which is now under construction, the knowledge of erosion processes and the behaviour of various constructional materials under extreme conditions is a very critical issue, which will determine a successful realization of the project. The most important plasma–surface interaction (PSI) effects in 3D geometry have been studied using a QSPA Kh-50 powerful quasi-stationary plasma accelerator. Mechanisms of the droplet and dust generation have been investigated in detail. It was found that the droplets emission from castellated surfaces has a threshold character and a cyclic nature. It begins only after a certain number of the irradiating plasma pulses when molten and shifted material is accumulated at the edges of the castellated structure. This new erosion mechanism, connected with the edge effects, results in an increase in the size of the emitted droplets (as compared with those emitted from a flat surface). This mechanism can even induce the ejection of sub-mm particles. A concept of a new-generation QSPA facility, the current status of this device maintenance, and prospects for further experiments are also presented.